Quantum mechanical measurement in monistic systems theory - Klaus Fröhlich (Science & Philosophy, 2023)
The monistic worldview aims at a uniform description of nature based on scientific models. Quantum physical systems are mutually part of the other quantum physical systems. An aperture distributes the subsystems and the wave front in all possible ways. The system only takes one of the possible paths, as measurements show. Conclusion from Bell's theorem: Before the quantum physical measurement, there is no point-like location in the universe where all the information that explains the measurement is available. Distributed information is possible. Movement of the particle and measuring process are deterministic. The oscillation between location uncertainty and momentum uncertainty leads photons to determine their own location at short intervals. The uncertainty principle focuses the systems. The fields of the surrounding matter influence the location of the new formation. The effect of all fields is based on a common mechanism.